1976
DOI: 10.1210/jcem-42-5-976
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Suppression of Serum T3and T4

Abstract: Dexamethasone (2 mg q6h for 48 h) decreased serum T3 in normal and athyreotic subjects, and decreased T4 in normal subjects. Dexamethasone probably alters secretion and peripheral metabolism of thyroid hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…The effect on thyroid function has been previously described in humans (Wilber and Utiger 1969;Faglia et al 1973;Degroot and Hoye 1976) and in rats (Ranta 1975). The reduction in thyroxine secretion is probably due to a direct action on the pituitary and on the thyroid.…”
Section: Discussionmentioning
confidence: 74%
“…The effect on thyroid function has been previously described in humans (Wilber and Utiger 1969;Faglia et al 1973;Degroot and Hoye 1976) and in rats (Ranta 1975). The reduction in thyroxine secretion is probably due to a direct action on the pituitary and on the thyroid.…”
Section: Discussionmentioning
confidence: 74%
“…This may be due to the relative amelioration of glucocorticoid deficiency by relieving acute stress mainly caused by infection, as observed previously by Dexter [18]. Although pharmacological doses of glucocorticoids have been reported to depress serum T3 in man [17,19] and to inhibit iodide uptake into FRTL-5 rat thyroid cells [9], this case as well as cases in the literature may indicate that a physiological dose of glucocorticoid is needed for the synthesis or secretion of thyroid hormone under stimulation by TSH. Furthermore, none of the patients with a normal pituitary-thyroid axis was reported as possessing antithyroid antibodies, whereas cases with pituitary-thyroid abnormality had a high incidence of these antibodies (Table 2).…”
Section: Discussionmentioning
confidence: 75%
“…propylthiouracil (23,24), glucocorticoids in high doses (25)(26)(27), certain radiographic contrast media (28,29), and the beta adrenergic blocking agents, propranolol (30) and amiodarone (31). It has generally been assumed that all of these factors act primarily to decrease production of T3 from T4, rather than to increase peripheral degradation ofT3, and direct studies have shown this to be true in the case of cirrhosis (5,22), fasting (12,32), and diabetes (15).…”
mentioning
confidence: 99%